2023
DOI: 10.1111/jmwh.13475
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Reduce Inpatient and Discharge Opioid Prescribing for Postpartum Patients: A Systematic Review

Abstract: Introduction As deaths related to opioids continue to rise, reducing opioid use for postpartum pain management is an important priority. Thus, we conducted a systematic review of postpartum interventions aimed at reducing opioid use following birth. Methods From database inception through September 1, 2021, we conducted a systematic search in Embase, MEDLINE, Cochrane Library, and Scopus including the following Medical Subject Heading (MeSH) terms: postpartum, pain management, opioid prescribing. Studies publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…This lower use likely reflects a general focus on decreasing opioid use at OSU Wexner Medical Center as well as nationally. 43 Nevertheless, our study showed a 53% decrease in inpatient postoperative MME use in the active device group. The opioids prescribed at discharge differed by a median of 7.5 MME, which equates to approximately 1 fewer 5-mg oxycodone tablet per individual treated with the functional device.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…This lower use likely reflects a general focus on decreasing opioid use at OSU Wexner Medical Center as well as nationally. 43 Nevertheless, our study showed a 53% decrease in inpatient postoperative MME use in the active device group. The opioids prescribed at discharge differed by a median of 7.5 MME, which equates to approximately 1 fewer 5-mg oxycodone tablet per individual treated with the functional device.…”
Section: Discussionmentioning
confidence: 51%
“…This lower use likely reflects a general focus on decreasing opioid use at OSU Wexner Medical Center as well as nationally. 43 Nevertheless, our study showed a 53% decrease in inpatient postoperative MME use in the active device group.…”
Section: Strengths and Limitationsmentioning
confidence: 51%
“…These policies have implications for healthcare delivery, including anesthesia services, and highlight the intersection of public health policies and healthcare regulation. The ERACS protocol, endorsed by the Society for Obstetric Anesthesia and Perinatology (SOAP), has been recognized as a pathway for postoperative care in cesarean delivery (Badreldin et al, 2023;Bollag et al, 2021;Macones et al, 2019;Sultan et al, 2022Sultan et al, , 2023Zanolli et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the simplicity of our opioid stewardship programme, a large retrospective study by Reed et al 16 demonstrated that the majority of patients did not receive multimodal analgesia after caesarean delivery in the USA 16. In addition, current evidence shows that different interventions can effectively reduce postpartum opioid use, but there is no optimal method yet 17. Therefore, we believe our programme applies in different contexts but requires continuous evaluation and adjustments over time.…”
Section: Discussionmentioning
confidence: 97%
“…16 In addition, current evidence shows that different interventions can effectively reduce postpartum opioid use, but there is no optimal method yet. 17 Therefore, we believe our programme applies in different contexts but requires continuous evaluation and adjustments over time.…”
Section: Open Accessmentioning
confidence: 99%